Operations Management of Logistics and Supply Chain: Issues and Directions - Xiang Li (Discrete Dynamics in Nature and Society)
There has been consensus that logistics as well as supply chain management is a vital research field, yet with few literature reviews on this topic. This paper sets out to propose some hot issues in the current research, through a review of related literature from the perspective of operations management. In addition, we generate some insights and future research directions in this field.